Community, adaptability, and good judgement: Reflections on creating meaningful, sustainable pedagogy in uncertain times. (1st January 2021) - Brown, Gary; McCall, Victoria
Abstract : This reflective piece details aspects of pedagogic good practice prompted by our experiences of developing online learning in the context of the COVID-19 pandemic. Given the exceptional circumstances experienced by universities globally, and given the unprecedented challenges continuing to face educators, new, distinctive methods of delivering a high-quality student experience, to tight time constraints were required. We reflect upon our experiences of engaging in COVID-19 planning, drawing from our substantial knowledge of delivering postgraduate education in the online environment, offering three aspects of good practice (establishing community, adaptability, and good judgement), sometimes taken for granted or overlooked, relevant not only in exceptional circumstances but, as we also suggest in the paper, important to university educators seeking to deliver high-quality, sustainable pedagogy more broadly. The aspects of good practice we outline are mutually reinforcing, unlikely in their own right to deliver the beneficial, sustainable outcomes apparent when embedded in combination.